Risk Factors for and Mechanisms of COlistin Resistance Among Enterobacterales: Getting at the CORE of the Issue. (21st April 2021) - Mills, John P; Rojas, Laura J; Marshall, Steve H; Rudin, Susan D; Hujer, Andrea M; Nayak, Luke; Bachman, Michael A; Bonomo, Robert A; Kaye, Keith S
Abstract: Background: Despite the recent emergence of plasmid-mediated colistin resistance, the epidemiology and mechanisms of colistin-resistant Enterobacterales (CORE) infections remain poorly understood. Methods: A case–case–control study was conducted utilizing routine clinical isolates obtained at a single tertiary health system in Ann Arbor, Michigan. Patients with CORE isolates from January 1, 2016, to March 31, 2017, were matched 1:1 with patients with colistin-susceptible Enterobacterales (COSE) and uninfected controls. Multivariable logistic regression was used to compare clinical and microbiologic features of patients with CORE and COSE to controls. A subset of available CORE isolates underwent whole-genome sequencing to identify putative colistin resistance genes. Results: Of 16 373 tested clinical isolates, 166 (0.99%) were colistin-resistant, representing 103 unique patients. Among 103 CORE isolates, 103 COSE isolates, and 102 uninfected controls, antibiotic exposure in the antecedent 90 days and age >55 years were predictors of both CORE and COSE. Of 33 isolates that underwent whole-genome sequencing, a large variety of mutations associated with colistin resistance were identified, including 4 mcr -1/ mcr -1.1 genes and 4 pmrA/B mutations among 9 Escherichia coli isolates and 5 mgrB and 3 PmrA mutations among 8 Klebsiella pneumoniae isolates. Genetic mutations found in Enterobacter species were not associated with known phenotypic colistin resistance. Conclusions: Increased age and prior antibiotic receipt were associated with increased risk for patients with CORE and for patients with COSE. Mcr -1, pmrA/B, and mgrB were the predominant colistin resistance–associated mutations identified among E. coli and K. pneumoniae, respectively. Mechanisms of colistin resistance among Enterobacter species could not be determined.